Melanoma Cells Homing to the Brain: An In Vitro Model. (26th January 2015) - Rizzo, A.; Vasco, C.; Girgenti, V.; Fugnanesi, V.; Calatozzolo, C.; Canazza, A.; Salmaggi, A.; Rivoltini, L.; Morbin, M.; Ciusani, E.
Abstract : We developed an in vitro contact through-feet blood brain barrier (BBB) model built using type IV collagen, rat astrocytes, and human umbilical vein endothelial cells (HUVECs) cocultured through Transwell porous polycarbonate membrane. The contact between astrocytes and HUVECs was demonstrated by electron microscopy: astrocytes endfeet pass through the 8.0 μ m pores inducing HUVECs to assume a cerebral phenotype. Using this model we evaluated transmigration of melanoma cells from two different patients (M1 and M2) selected among seven melanoma primary cultures. M2 cells showed a statistically significant higher capability to pass across the in vitro BBB model, compared to M1. Expression of adhesion molecules was evaluated by flow cytometry: a statistically significant increased expression of MCAM, α v β 3, and CD49b was detected in M1. PCR array data showed that M2 had a higher expression of several matrix metalloproteinase proteins (MMPs) compared to M1. Specifically, data suggest that MMP2 and MMP9 could be directly involved in BBB permeability and that brain invasion by melanoma cells could be related to the overexpression of many MMPs. Future studies will be necessary to deepen the mechanisms of central nervous system invasion.